Building Critical System Thinking Capability in Engineering Students: A Case for Long- Term Tech Internships on Campus - Gupta, Ankur; Sawhney, Sahil; Nanda, Ankita; Gupta, Adit (Journal of Engineering Education Transformations, 2026)
The rapidly evolving technology and business landscape necessitates the development of critical systems thinking skills among graduates to tackle complex, real-world challenges. This quantitative longitudinal study, spanning two years, explores the effectiveness of on-campus tech internships in enhancing systems thinking skills among 30 selected STEM students. Guided by expert mentors in system design, the internships addressed authentic problems with clear deliverables, supported by training, resources, access to facilities, and incentives for attaining pre-defined outcomes. Critical systems thinking was assessed using two parallel versions of the Engineering Systems Thinking Assessment (ESTA) to avoid familiarity bias, complemented by project journal evaluations on a continuous basis. Statistical analyses, including paired t-tests and ANOVA, demonstrated a significant enhancement in ESTA scores (p < 0.001), alongside notable outcomes: qualitative improvements in placement quality, patents filed, and improved standing in external hackathons. These results highlight the potential of long-term tech internships as a viable strategy to bolster graduate attributes, at least in small cohorts to begin with.